Pengaruh Lama Penundaan Pemeriksaan Serum Terhadap Kadar Elektrolit Natrium dan Klorida: The Effect of Delayed Serum Examination on Sodium and Chloride Electrolyte Levels - Azizah, Nurul; Aliviameita, Andika (Medicra (Journal of Medical Laboratory Science/Technology), 2019)
Electrolytes play an important role in the human body that can affect metabolism. Sample handling more than two hours in examination electrolyte levels would lead to less accurate results. This study aims to determine the effect of long delays serum examination of the levels of electrolytes sodium and chloride for 0, 3, 5, and 7 hours. This research was conducted with an experimental method using 32 serum samples. Results of sodiumand chloride levels after an increase in deferred examination. The mean 0 hour sodium level is 142.55 mmol/L, 3-hour sodium level is 143.18 mmol/L, 5-hour sodium level is 143.91 mmol/L and 7-hour sodium level is 144.41 mmol/L. The mean 0 hour chloride level is 97.66 mmol/L, 3-hour chloride level is 99.96 mmol/L, 5- hour chloride level is 103.62 mmol/L and 7-hour chloride level is 107.55 mmol/L. This study reflected thatthere is no effect of delaying serum on sodium levels, and there is an effect of delaying serum on chloride levels.